A clinical case of CADASIL syndrome in a patient after a new coronavirus infection COVID-19 - Z. Sh. Dzhalilova; E. A. Gavrilova; A. A. Yakovlev; A. G. Smochilin (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2023)
CADASIL-cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy is the most common form of hereditary cerebral angiopathy and is characterized by recurrent subcortical ischemic strokes, migraine with aura, and cognitive impairment. The article presents clinical case of the female patient with newly diagnosed CADASIL syndrome, who was admitted to the clinic for a course of rehabilitation treatment three months after the onset of an acute cerebrovascular accident caused by a combination of congenital and infectious angiopathy. The combination of CADASIL syndrome and coronavirus infection COVID-19 caused by the SARS-CoV-2 manifested by an acute cerebrovascular accident and the occurrence of focal neurological signs. There was a positive trend in the form of a partial regression of neurological signs against the background of repeated courses of rehabilitation treatment, including physical exercises, mechanotherapy, physiotherapy and acupuncture.